The Diagnostic Challenge of Eosinophilic Granulomatosis With Polyangiitis Presenting as Acute Eosinophilic Myocarditis: Case Report and Literature Review - Yamamoto, Hiroyuki; Hashimoto, Katsuya; Ikeda, Yoshihiko; Isogai, Jun; Hashimoto, Toru (Frontiers in Cardiovascular Medicine, 2022)
Eosinophilic granulomatosis with polyangiitis (EGPA) is a systemic vasculitis involving small-to-medium-sized vessels characterized by asthma, vasculitis, and peripheral eosinophilia. EGPA-associated eosinophilic myocarditis (EM) occurs rarely, yet can be fatal if left untreated. Moreover, the accurate diagnosis of EGPA-associated EM without vasculitis is exceptionally difficult because of the overlapping features with EM of other causes. We report a case of probable EGPA with subclinical neurological involvement that presented with acute EM. The constellation of peripheral eosinophilia, left ventricular dysfunction, and normal epicardial coronary arteries raised suspicion of acute EM, which was confirmed by cardiac magnetic resonance (CMR) investigation and endomyocardial biopsy (EMB). Prompt systemic administration of corticosteroids completely restored and normalized myocardial structure and function. Although the patient's history suggested the presumed hypersensitivity myocarditis, EMB revealed EM without vasculitis, not hypersensitivity, leading to a tentative diagnosis of idiopathic hypereosinophilic syndrome. Interestingly, the characteristic findings of vasculitis on CMR imaging strongly suggested EGPA-associated EM. Although the patient had no clinical neurological manifestations, a nerve conduction study confirmed mononeuritis multiplex, leading to the final diagnosis of probable EGPA. Therefore, this case highlights the diagnostic challenge associated with EGPA and the diagnostic synergy of CMR and EMB for an exploratory diagnosis of EGPA-associated EM.